SCHOOL OF HUMAN RESOURCE AND DEVELOPMENT DEPARTMENT OF SOCIAL SCIENCES AND HUMANITIES - MWANGI, Dr. M. KAMAU (IJRDO - Journal of Applied Management Science, 2015)
This paper looks at the various media policy engagements in Kenya from the onset ofcolonialism, through the various administrations in the post-colonial era to the present. Thepurpose of the paper is to examine the circumstances that have informed the media policychanges through the period Kenya has been in existence as a modern nation. The paper drawsmainly from primary sources including papers and published books on how media has beentreated by successive administrations in Kenya. It has shown how the much sought mediafreedom has been continually elusive, and even after the promulgation of the new constitutionwhich gave wide latitude for media operations, other roadblocks in the name of conglomeration,concentration and cross-media ownership have come into play to complicate the equation. Thestudy concludes by underlining the importance of a free and unhindered media and recommendsthe way forward in the formation of an oversight body as the new constitution directs.